The Rescue: A Romance of the Shallows - Conrad, Joseph, 1857-1924 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Rescue: A Romance of the Shallows" by Joseph Conrad is a novel published in 1920. Captain Tom Lingard commands a sailing ship in the Malayan archipelago, committed to helping his native friend Hassim reclaim his land. When he encounters a stranded yacht, Lingard meets the enigmatic Edith Travers, wife of a hostile British gentleman. As romantic tension builds between Lingard and Mrs. Travers, his loyalty to Hassim clashes with unexpected complications, forcing him to navigate treacherous waters between duty, friendship, and desire. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Rescue_(Conrad_novel)
Release date is 2006-01-09
Produced by Judy Boss and David Widger
Keywords: Sea stories; Love stories; Rescues -- Fiction; Lingard, Tom (Fictitious character) -- Fiction; Yachting -- Fiction; Malay Archipelago -- Fiction